SOSIALISASI DAMPAK PERNIKAHAN DINI MELALUI MEDIA FILM PENDEK - Murjainah Murjainah; Nina Damayati; Monanisa Monanisa; Laili Rosita; Mirna Taufik; Nuranisa Nuranisa; Deni Puji Hartono (LP4MK STKIP PGRI Lubuklinggau, 2021)
The aims of community service activities is to provide students understanding and awareness of the impact of early marriage through film media. The method used in community service is using the counseling method. The results of the analysis of PKM activities that have been carried out as a whole show a percentage of 76.5% included in the category of understand the concept of marriage. Then, students' perceptions of the effects of early marriage look quite good where students disagree with early marriage behavior, early marriage adversely affects reproductive health, marriage requires maturity both physically and mentally and readiness for marriage, early marriage is vulnerable Domestic violence and divorce, and understanding marriage is very important before deciding to get married. The importance of PKM activities is carried out further into schools as an effort to reduce the perpetrators of early marriage and the impact of early marriage.